Hubungan antara Profil Lipid dan Indeks Massa Tubuh dengan HbA1c pada Pasien Diabetes Melitus Tipe 2 di Poli Penyakit Dalam Rumah Sakit Umum Daerah Cibabat - Ariefa Rachma Putri; Herri S Sastramihardja (Bandung Conference Series: Medical Science, 2023)
Abstract. Diabetes mellitus (DM) is a chronic disease characterized by increased blood glucose and HbA1c levels due to impaired insulin hormone production or insulin resistance in the tissues. Insulin resistance is related to increased levels of fat in the body, which can occur in obesity and dyslipidemia. The purpose of this study was to assess the relationship between lipid profile and body mass index (BMI) with HbA1c in type 2 DM patients. This research was reviewed by the Ethics Committee of the Islamic University of Bandung with letter number 044/KPEK-Unisba/IV/2022. This type of research is quantitative observational analytic with a cross-sectional approach. Sampling was carried out by non-probability sampling with a total sampling technique. Data analysis was performed using the Chi-Square test. There were 48 samples, most of whom showed normal total cholesterol (52.1%) and normal triglycerides (60.4%), high LDL (54.2%) and low HDL (47.9%). The results showed that most of the patients had BMI in the pre-obese category (43.8%). It was also found that the majority of patients had HbA1c levels in the diabetic category (81.3%). Most of the patients with normal total cholesterol (47.1%) and triglyceride levels (47.1%) had diabetic HbA1c levels. Most patients with low HDL (44%) and high LDL (41.6%) levels had HbA1c levels in the diabetic category and most patients with normal BMI (27.1%) and pre-obese (33.3%) had HbA1c level for diabetes category. It was concluded that there was a relationship between lipid profile and HbA1c (p = 0.017) and there was a relationship between BMI and HbA1c (p = 0.000) in type 2 DM patients at the Internal Medicine Polyclinic at Cibabat Hospital for the period 2018–2021. The effect of HbA1c on the lipid profile occurs through the process of glycosylation. Keywords: Body Mass Index, HbA1c, Lipid Profile, Type 2 Diabetes Mellitus. Abstrak. Diabetes melitus (DM) merupakan penyakit kronis yang ditandai dengan peningkatan kadar glukosa darah dan HbA1c akibat gangguan produksi hormon insulin atau resistensi insulin di jaringan. Resistensi insulin diantaranya berkaitan dengan peningkatan kadar lemak dalam tubuh yang dapat terjadi pada obesitas dan dislipidemia. Tujuan penelitian ini menilai hubungan antara profil lipid dan indeks massa tubuh (IMT) dengan HbA1c pada pasien DM tipe 2. Penelitian ini telah dikaji oleh Komite Etik Universitas Islam Bandung dengan nomor surat 044/KPEK-Unisba/IV/2022. Jenis penelitian ini adalah kuantitatif observasional analitik dengan pendekatan cross sectional. Pengambilan sampel dilakukan secara non-probability sampling dengan teknik total sampling. Analisis data dilakukan menggunakan uji Chi-Square. Sampel berjumlah 48 yang sebagian besar memperlihatkan kadar kolesterol total normal (52,1%) dan trigliserida normal (60,4%), LDL tinggi (54,2%), dan HDL rendah (47,9%). Hasil penelitiaan menunjukkan sebagian besar pasien memiliki IMT kategori pre-obesitas (43,8%). Didapatkan pula sebagian besar pasien memiliki kadar HbA1c kategori diabetes (81,3%). Sebagian besar pasien dengan kadar kolesterol total (47,1%) dan trigliserida normal (47,1%) memiliki kadar HbA1c kategori diabetes. Sebagian besar pasien dengan kadar HDL rendah (44%) dan LDL tinggi (41,6%) memiliki kadar HbA1c kategori diabetes dan sebagian besar pasien dengan kategori IMT normal (27,1%) dan pre-obesitas (33,3%) memiliki kadar HbA1c kategori diabetes. Didapatkan kesimpulan bahwa terdapat hubungan antara profil lipid dan HbA1c (p = 0,017) dan terdapat hubungan antara IMT dan HbA1c (p = 0,000) pada pasien DM tipe 2 di Poli Penyakit Dalam RSUD Cibabat periode tahun 2018–2021. Pengaruh HbA1c terhadap profil lipid terjadi melalui proses glikosilasi. Kata Kunci: Diabetes Melitus tipe 2, HbA1c, Indeks Massa Tubuh, Profil Lipid